Socio-Economics Importance and Its Determinant Factors of Wetlands in Eastern Ethiopia - Abu Mulatu; Jemal Herko; Shiferaw Alem (CV. Literasi Indonesia, 2023)
Wetland in Ethiopia provides various socio-economic benefits for the local community and for the people who live around the ecosystem. Despite this, the wetland in Ethiopia provides various benefits to the local community, it is under severe pressure and degradation from natural causes and human activity. The present study aims to assess the socio-economic importance of the wetland that existed in the East Harerghe zone. Both primary and secondary data were employed to answer the study objective. Accordingly, a total of 220 respondents were selected to administer the questionnaire. SPSS version 20 was used for data analysis and a multiple regression model was used to see the relationship between dependent and independent variables. The income generated varies in two lakes, Lake Langie is 56,196.8 birr, whereas the mean annual income in Lake Adele is 54,662.6 birr. The determining factor for the income generated from the wetland is the respondent land size and the distance between the wetland and farmland. Among respondents, 53.2% of the respondents perceived that the lakes are highly degraded followed by less degraded 33.9% and 12.6% in good condition. Agricultural expansions are indicated as the major triggering factor for the degradation of wetlands followed by population pressure, sedimentation, deforestation, overgrazing, and poor law enforcement and regulation respectively. Most respondents are interested in participating in conservation activity and the recommended activity to tackle this degradation is soil and water conservation and tree planting activity.